Electric Motor Maintenance: Pemeliharaan Motor Listrik - Hasfi, Akbar Rayhan; Syahrorini, Syamsudduha (Universitas Muhammadiyah Sidoarjo, 2024)
Electric motors play a vital role in industrial operations, and their protection from overloading is crucial for ensuring longevity, safety, and efficiency. This article explores the significance of motor overload protection devices in safeguarding motors from damage caused by overloading, which can lead to overheating and potential failure. It discusses the functioning of various protection devices, such as thermal, magnetic, and electronic overload relays, and emphasizes the importance of selecting the right device based on motor type, size, application, and environmental conditions. The article also highlights the role of regular maintenance and adherence to safety standards in ensuring the reliable and effective functioning of these protection systems. By implementing appropriate protection measures, companies can optimize energy use, increase operational efficiency, and reduce damage and production disruptions, thus contributing to the sustainability and safety of electric motors in industrial settings vulnerable to overloading. Highlight : Overload relays protect the motor, motor branch circuit, and motor branch circuit components from excessive heat from the overload condition Overload relays are part of the motor starter and protect the motor by monitoring the current flowing in the circuit The selection of an overload relay is important because repeated tripping and reset can reduce the mechanical life of the relay and may cause damage to the motor Keywords: electric motors, overload protection devices, thermal overload relays, magnetic overload relays, electronic overload relays, motor type.